Independence as a Moderator of the Influence of Integrity and Objectivity on Audit Quality - Dewi Utami (Jurnal Ekonomi, 2024)
This study aims to analyze respondents' perceptions of integrity, objectivity, independence, and audit quality, as well as how these factors interact and affect audit quality. Based on the analysis results, it was found that respondents' perceptions of integrity, objectivity, independence, and audit quality were in the satisfactory category. The instrument testing showed that the research instruments have very good validity and reliability and are suitable for use in this study. The results of the moderating regression analysis indicate that integrity and independence have a significant impact on audit quality. Furthermore, it was found that independence can significantly enhance the relationship between integrity and audit quality. Conversely, the results show that objectivity partially does not affect audit quality, and independence does not strengthen the relationship between objectivity and audit quality. These findings provide important insights for audit practices, highlighting the importance of integrity and independence in improving audit quality, while the role of objectivity needs to be further reviewed to understand its insignificant impact.